Diseño del sistema integrado de gestión QHSE para car Hyundai S.A. – Bogotá D.C. (2015)
The purpose of this project was to design the integrated QHSE management system for Car Hyundai S.A. It was developed in the Car Hyundai facilities located in the Autopista Norte, Calle 233, Costado Occidental in the city of Bogotá in the after-sales service, to respond to the need to establish clear guidelines regarding the quality of the services provided, know and manage environmental aspects and impacts derived from the processes carried out, and the identification of hazards present in the activities and the management of risks. The investigation was framed in an exploratory-descriptive methodology approach. For the collection of the information, the interview technique was used, whose instrument was the checklist applied to key persons to identify the main processes, aspects and environmental impacts and the dangers present in the after-sales process. Likewise, a checklist was used, leveraging the techniques of observation and interview, in order to determine the degree of non-compliance with the requirements of the standards NTC-ISO 9001: 2008, NTC-ISO 14001: 2004, NTC-OHSAS 18001: 2007 and Decree 1443 of 2014 repealed by Decree 1072 of 2015. Then the system integration was presented, for which a table containing the correspondences of the requirements of the standards was created, indicating which the company owns, which must be developed and which ones are presented as an option of the integrated management system. Once the information collected was analyzed, the feasibility of integrating quality, environmental, and occupational health and safety management systems was determined, provided that the company has the necessary resources. The work to be done for the integration will be arduous especially in the environmental aspect, whose percentage of compliance with the requirements is low. With regard to occupational health and safety, in one way or another, the requirements must be met, since these are regulated by Decree 1072 of 2015. In any case, the success of the system will depend on commitment and participation. active of each and every one of the members of the company and in this way establish and maintain the integrated QHSE management system.